2020
DOI: 10.1016/j.polymer.2020.122825
|View full text |Cite
|
Sign up to set email alerts
|

Poly(alkylene 2,5-furanoate)s thin films: Morphology, crystallinity and nanomechanical properties

Abstract: Poly(alkylene 2,5-furanoate)s are considered as the most attractive and interesting alternatives to replace oil-based terephthalic polymers. These furan-based polyesters can be synthesized using fully bio-based synthetic strategies, allowing to reduce the environmental impact of plastics. At the same time, these polymers have shown outstanding thermal, mechanical and gas-barrier properties. All these results envisage their industrial use in the near future. Now, considering the downscaling of the products' siz… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 66 publications
1
19
0
Order By: Relevance
“…This result is in line with recent AFM observations of PPeF crystallization in thin film geometry, where crystalline structures started appearing after 3 months of storage at room temperature. 55 To provide further information about the crystallization behavior of bulk PPeF, in our current work we performed DSC and XRD studies of a freshly prepared sample as a function of the storage time, as presented in Figure S1. There, it is observed that the PPeF film requires about 4 months to develop some detectable crystalline structures.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This result is in line with recent AFM observations of PPeF crystallization in thin film geometry, where crystalline structures started appearing after 3 months of storage at room temperature. 55 To provide further information about the crystallization behavior of bulk PPeF, in our current work we performed DSC and XRD studies of a freshly prepared sample as a function of the storage time, as presented in Figure S1. There, it is observed that the PPeF film requires about 4 months to develop some detectable crystalline structures.…”
Section: Discussionmentioning
confidence: 99%
“…23,25 Specifically, the different number of methylene groups has a direct effect on the chain mobility and crystallizing capability. 23,[55][56] These characteristics allow to obtain from amorphous to semicrystalline polymers, which at room temperature can be in the glassy or in the rubbery state. According to these features, a different microstructure can develop, having a direct effect on the macroscopic properties.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this case, complex time-dependent flow fields, temperature and pressure generate intricate morphologies with process specific features [20,21]. A large number of studies on micro and nano characterizations make reference to a variety of polymer materials ranging from highly crystalline polymers [22,23] to low-crystallinity and glassy polymers [24]. However, due to the small size and complexity of the features developed during common processing conditions, an extensive application of these methods requires additional studies.…”
Section: Introductionmentioning
confidence: 99%